Screening recipients of increased‐risk donor organs: a survey of transplant infectious diseases physician practices. Issue 5 (31st July 2013) - Theodoropoulos, N.; Ladner, D.P.; Ison, M.G.
Abstract: Background: In 1994, the Public Health Service published guidelines to minimize the risk of human immunodeficiency virus (HIV) transmission and to monitor recipients following the transplantation of organs from increased‐risk donors. A 2007 survey revealed the post‐transplant surveillance of recipients of organs from increased‐risk donors (ROIRD) is variable. Methods: An electronic survey was sent to transplant infectious diseases physicians at US solid organ transplant centers. Results: A total of 126 surveys were sent to infectious diseases physicians, and we received 51 (40%) responses. We found that 22% of respondents obtain only verbal, 69% verbal and written, and 8% do not obtain any special consent from ROIRD, despite an Organ Procurement and Transplantation Network policy requiring such consent. Post‐solid organ transplantation serologies for HIV, hepatitis B virus (HBV), and hepatitis C virus (HCV) are performed by 6–8% of respondents in all recipients, by 69% of respondents in ROIRD only, and 25% of respondents do not perform them at all. Post‐transplant nucleic acid testing is carried out by 55–64% of respondents in ROIRD, by 0–2% in all recipients, and not performed by 35–43% of respondents. Conclusion: Screening RIORD for HIV, HBV, and HCV has increased since 2007, but remains less than optimal and is incomplete when screening for disease transmission at many centers.